Analisis Usability Web E-Learning STKIP Bangkalan sebagai Media Pembelajaran Daring dengan Metode Usability Testing - Viola Budi Antika; Prita Dellia; Diana Syifah; Dewi Kusuma Wardani; Muhammad Alfis Sholikhin (Lembaga Pengembangan Kinerja Dosen, 2025)
This study analyzes the usability of the STKIP Bangkalan e-learning website as an online learning medium using the System Usability Scale (SUS) method. The evaluation covers five aspects of usability, namely learnability, efficiency, memorability, errors, and satisfaction, through a questionnaire filled out by students. The title